Written for Children and Written for the Adults: the Interralation in Mayakovsky’s Poetry - Zamyatina, Oksana (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2020)
The article is devoted to comparing Mayakovsky’s “adult” texts with his poems written for children. Having analyzed three of the latter – “A Fairy Tale About Petya, a Fat Boy, and Sima, Who Is Thin” (1925), “The Little Book About the Seas and the Lighthouse” (1926) and “The Fire Horse” (1927) – the author concludes that Mayakovsky’s texts for children (although simpler and less complicated in terms of employed imagery) follow the logic of development of the mythological images which are fundamental for the entire work of the poet. They include: the image of face(s), the collective body, “fat” and “fatness” as characteristics of the antagonist, an opposition between “the voice” and “the fat”. The conducted comparison makes it possible to gain another point of view on the deceptively simple images and plots in Mayakovsky’s poems for children. It makes it possible to note how poetic constants pass from texts of one status to texts from another group, with the most important structural principles fully preserved.